An influenza outbreak in a South African mine, following the relaxation of COVID-19 pandemic restrictions, September – December 2021 - Fiona Els; Mariana Khoza; Inge Kleinhans; Hetani Mdose; Sibongile Walaza; Cheryl Cohen; Anne von Gottberg; Fahima Moosa; Mignon du Plessis; Nicole Wolter; Chijioke Nkemjika Umunnakwe; Zinhle Makatini; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: In November 2021, two months after lifting COVID-19 restrictions, a cluster of laboratory-confirmed influenza cases was detected outside of the normal influenza season at a mine in South Africa. We aimed to determine factors associated with influenza infection.